How climate change affected on water level in Ha Long coastal area in the period 1974–2020: results from the mann-kendall test and sen’s slope estimate - Nguyen Minh, Hai; Vu Duy, Vinh (Vietnam Journal of Marine Science and Technology, 2022)
The impact of climate change on sea level has attracted much attention from scientists worldwide. The analysis of sea-level change at global and regional scales is based on altimetry and/or tide gauge data. The main objective’s study relied on statistical tests to highlight the significant long-term changes in sea level in Ha Long coastal area through the 47 years (1974–2020) historical tide gauge record of the Bai Chay station. The average water level in this area was 207.9 cm, which tended to be higher in recent years, especially from 2006 to the present (above 210 cm). Moreover, sea level trends were carried out separately for the whole period (1974–2020) and the last 19 years (2002–2020) by the Mann-Kendall test and Sen’s slope estimator. The results showed a significant sea-level rise (SLR) trend with a 95–100% confidence level. The average annual rates of sea-level were 3.14 mm/year and 5.83 mm/year in 1974–2020 and 2002–2020, respectively, indicating an SLR of about 14.76 cm over 47 years and significant acceleration in SLR recently (11.01 cm over the last 19 years).